Desenvolvimento Territorial e gestao participativa: o caso do Projeto Microbacias 2, em três Barras/Sc - Matykevicz, Roselaine (2007)
The aim of this dissertation is to analyze the process of participative management of the Project Micro Basins 2 implanted in two micro basins in the county of Três Barras/SC.This project is based on the tripod includes economic, environmental and social aims, it also presents strategies of actions which praises the development of a participative process. It is tried to understand the increasingly interest in the valorization of the participative element recording its relationship with the tendency, today, of approaching the territorial development. The same way, it has been tried to get previous experiences, which have influence in the present position of the Project. Hence, there is evidence that the strategy of action of the Project Micro Basin 2, is based on an innovative proposal for the reality studied, and that this process presents, at the same time, positive aspects which register the emphasis of the participative management and limiting appearances manly for not assume a territorial approach of the development. The opening of participative spaces, the boosted pedagogic feasibility, the possibility to accept more the local priorities, the insertion of new social behaviour characterize themselves as positive factors. On the other hand the incompatibility between the Project proposal and the local historical and social aspects, the adoption of hydrographic basins as a unit of operation and the record of operational problems have appeared to be the main problems of the process. It is , then, asked if the participative management proposal taken by the Project Micro Basins 2 is an authentic participation. So evidently, the studied case, for not presenting the participation and the autonomy desired, it consists more precisely in a process of pseudo participation.